Functional outcomes of accelerated rehabilitation protocol for anterior cruciate ligament reconstruction in amateur athletes: a randomized clinical trial - Omar M. Elabd; Ahmad H. Alghadir; Abeer R. Ibrahim; Shahnaz Hasan; Moattar R. Rizvi; Ankita Sharma; Amir Iqbal; Aliaa M. Elabd (Medical Journals Sweden, 2024)
Objective: To determine the impact of the accelerated rehabilitation protocol on knee pain in amateur athletes with anterior cruciate ligament reconstruction (ACLR). Design: Two-arm, parallel-group randomized comparative design. Patients: 100 amateur male athletes (mean age22.01±1.79) with ACLR were randomly divided into experimental and control groups (n=50/group). Methods: An accelerated rehabilitation protocol and a conventional one were used for the experimental group. In contrast, only the conventional rehabilitation protocol was used for the control group in five weekly sessions for twenty-two weeks. The primary outcome measure, knee pain, was measured using the visual analog scale (VAS). Extensive test batteries for hop tests, Knee Injury and Osteoarthritis Outcome Score (KOOS), and knee effusion were measured, aiming to add more objective criteria to determine functional performance. Results: Both groups (n=50/group) were well-matched (p=0.816), with insignificant differences in their demographic characteristics (p>0.05). MANOVA test showed no significant difference between the two groups (p=0.781) at baseline. A two-way MANOVA of within and between groups' variations indicated overall significant treatment, time, and treatment × time interaction effects (p<0.001) in favor of the accelerated rehabilitation group. Conclusions: The accelerated rehabilitation protocol was more effective in improving functional outcomes than a conventional one in amateur athletes with ACLR.